Study on the Legal and Contractual Obligations of Power Companies in Private EV Charging Pile Installation Request - Yiran Yang; Shiyao Tan; Yufei Zhu; Yan Luo (Studies in Law and Justice, 2025)
With the popularization of electric bicycles and new energy vehicles, the demand for private charging pile installation has surged. When users submit installation applications to power companies, disputes arise over whether the latter bears a mandatory contracting obligation. While power companies are obligated to contract under certain circumstances, this obligation has clear boundaries. When the owner does not have the installation conditions, the common parking space has not been agreed by all the owners, and the requirements of the electricity contract are unreasonable after review, the power company has the right to refuse the installation, and the dynamic balance rule of the power company’s review right and contracting obligation should be established. By creating a “power company technical review — property synergy management — owner rights protection” three-party linkage mechanism, practical and legally justified solutions can be provided for new energy infrastructure disputes.